2007
DOI: 10.1159/000101448
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Lupus Nephritis with Cyclosporine – An Outcome Analysis

Abstract: Background: The optimal therapy for lupus nephritis (LN), including the role of cyclosporine (CsA), still lacks scientifically valid clinical experience. We evaluated the efficacy of CsA in the induction and maintenance treatment of patients with biopsy-proven LN. Patients and Methods: A total of 31 patients (25 women, 6 men, mean age 29.5 years) were enrolled in the study. The majority had proliferative LN. The mean follow-up was 85.6 ± 24.7 months. Results: CsA was used as first-line treatment in 38.7% of pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 22 publications
0
14
0
1
Order By: Relevance
“…A long-term retrospective study has demonstrated high complete remission rates with long relapse-free intervals when CSA was used as a first-or second-line agent for LN (30). CSA was found to be equally effective as maintenance therapy for LN compared with azathioprine (31).…”
Section: Calcineurin Inhibitorsmentioning
confidence: 99%
See 2 more Smart Citations
“…A long-term retrospective study has demonstrated high complete remission rates with long relapse-free intervals when CSA was used as a first-or second-line agent for LN (30). CSA was found to be equally effective as maintenance therapy for LN compared with azathioprine (31).…”
Section: Calcineurin Inhibitorsmentioning
confidence: 99%
“…The most significant side effects of CSA are hypertension, hyperlipidemia, gingival hyperplasia, and hirsutism (25,27,30). Dose adjustments may be required due to the risk of nephrotoxicity.…”
Section: Calcineurin Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have recently suggested that cyclosporine A (CsA), a calcineurin inhibitor similar to Tac, might replace cytotoxic agents and reduce the dosage of concomitantly administered PDN for maintenance therapy in selected patients with lupus nephritis (Rihova et al, 2007;Moroni et al, 2008). It has been reported CsA treatment has beneficial effects in some pediatric patient with SLE resistant to conventional immunosuppressive therapy, including iv-CPA (Sakano et al, 2004;Suzuki et al, 2006).…”
Section: Tacrolimus a Calcineurin Inhibitormentioning
confidence: 99%
“…Aparte del perfil de nefrotoxicidad de los inhibidores de calcineurin a dosis altas y por periodos prolongados, un problema que se ha detectado con su administración es la alta tasa de recaídas posterior a su retiro, informándose en el estudio de Rihova valores cercanos al 46% 21 , creándose un grupo de pacientes dependientes de ciclosporina. Es importante también anotar que ante el riesgo que portan de empeorar la función renal se recomienda evitar la ciclosporina cuando la tasa de filtración glomerular es inferior a 60 ml/minuto y la biopsia renal demuestra severa fibrosis tubulointersticial.…”
unclassified